Effect of pulsed light treatment on the phytochemical, volatile, and sensorial attributes of lactic-acid-fermented mulberry juice. Issue 1 (1st January 2018) - Kwaw, Emmanuel; Ma, Yongkun; Tchabo, William; Apaliya, Maurice Tibiru; Sackey, Augustina Sackle; Wu, Meng; Xiao, Lulu
ABSTRACT: Lactic-acid-fermented mulberry juice (LFMJ) was subjected to pulsed light (PL) treatment at exposure time of 2, 4, and 8 s at high insensitive pulses of 14.0 J/cm 2 . The effect of PL treatment on the microbial inactivation, physicochemical, phytochemical, volatile, and sensory characteristics of LFMJ was evaluated. It was found that the PL was able to reduce the microbial load to acceptable levels (1.02 ± 0.04 log10 cfu/mL) with no significant impact on the physicochemical properties of LFMJ. It was also observed that the PL treatment caused a slight decrease in anthocyanin concentration at 8 s exposure time. The color difference (∆E) of the juice treated for 2 and 4 s fell below the slightly noticeable range 0.5<ΔE<1.5 while ∆E values for the 8 s (0.55 ± 0.02) and the thermal (0.50 ± 0.02) treated samples were slightly noticeable. The volatile profile and odor activity values were positively affected by increasing the exposure time. The results depict that, under the present experimental conditions, the application of the PL resulted in a fermented juice with superior quality attributes as compared to the thermal treated juice.